2020
DOI: 10.1055/a-1199-2378
|View full text |Cite
|
Sign up to set email alerts
|

Cardiovascular Biomarkers and Calculated Cardiovascular Risk in Orally Treated Type 2 Diabetes Patients: Is There a Link?

Abstract: AbstractThe aim of the study was to test the correlation of serum levels of asymmetric dimethylarginine (ADMA), endothelin 1 (ET-1), N-terminal brain natriuretic pro-peptide (NT-proBNP), and placental growth factor (PIGF-1) with estimated cardiovascular (CV) risk. The study group was composed of 102 women and 67 men with type 2 diabetes, having their glycemic and metabolic … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 51 publications
0
3
0
Order By: Relevance
“…This study showed that ADMA and PIGF-1 were not associated with CVR strati cation with any of the scores, while ET-1 was associated with the risk of stroke by the UKPDS and NT-proBNP was associated with CVR predicted by both tools. [39] Different from our research, these studies did not evaluate the female diabetic population, or the biomarkers analyzed by us.…”
Section: Discussionmentioning
confidence: 69%
See 1 more Smart Citation
“…This study showed that ADMA and PIGF-1 were not associated with CVR strati cation with any of the scores, while ET-1 was associated with the risk of stroke by the UKPDS and NT-proBNP was associated with CVR predicted by both tools. [39] Different from our research, these studies did not evaluate the female diabetic population, or the biomarkers analyzed by us.…”
Section: Discussionmentioning
confidence: 69%
“…[35] Few studies in the literature have attempted to correlate the use of biomarkers, especially those analyzed in the present study, and the CVR predicted by scores in the diabetic population. [36][37][38][39][40][41] One of these studies evaluated the association between a set of biomarkers that analyze different metabolic pathways, such as Asymmetric dimethylarginine (ADMA), Soluble endothelin-1 (ET-1), Placental growth factor-1 (PIGF-1) and NT-pro-BNP and the CVR predicted by the UKPDS and Action in Diabetes and Vascular disease (ADVANCE) scores in diabetic patients. This study showed that ADMA and PIGF-1 were not associated with CVR strati cation with any of the scores, while ET-1 was associated with the risk of stroke by the UKPDS and NT-proBNP was associated with CVR predicted by both tools.…”
Section: Discussionmentioning
confidence: 99%
“…A study on 169 patients with T2D evaluated the prognostic value of a series of alternative biomarkers including asymmetric dimethylarginine, a marker of endothelial dysfunction, endothelin‐1, an inflammatory marker and placental growth factor, another vascular index, along with NT‐proBNP 45 . Among these biomarkers, only NT‐proBNP was significantly correlated with the risk of coronary artery or cerebrovascular disease and the CV risk predicted by calculators such as the ADVANCE, the UKPDS 2.0 and the Framingham risk score.…”
Section: Performance Of Biomarkers For Predicting Incident Heart Fail...mentioning
confidence: 99%